Building sustainability and innovation in organizations. Issue 7 (5th February 2019) - Lazaretti, Kellen; Giotto, Olivo Tiago; Sehnem, Simone; Bencke, Fernando Fantoni
Abstract : Purpose: The purpose of this paper is to present the results of a systematic literature review on innovation and sustainability. To accomplish this aim, a systematic analysis of the literature in the Scopus database was carried out for articles with the terms "innovation" and "sustainability" in their titles. Once identified, articles were analyzed in three ways: the ten most-cited articles; the ten most-cited literature reviews; and the most recent articles. Sustainable development is the central theme of the articles studied. Sustainable development is influenced by the ways that sustainability is measured within the network of which the organizations are a part, including adequate systems, and is mediated by compatible behaviors. Encouraging green innovation is an environmental commitment and managerial concern driven by customer pressure, environmental regulations and cost reductions. Suppliers and customers can contribute or benefit from the value created. Design/methodology/approach: This study was a Systematic literature review. The search terms "Innov * AND sustain *" were defined for the titles of the articles. The analysis was divided into three categories: the ten most-cited articles (without a year filter to form an idea of the impact of the main research in the field); the ten most-cited reviews (these were only filtered from 2009 to 2018); and the 10 most recent articles (all of the articles found were from the year 2018). Findings: The main findings of this study were that network action, mobilization of relevant stakeholders, reinvention of the business model, redefinition with multiple values and a sustainable strategic scope are the mechanisms that effectively contribute to promoting the link between innovation and sustainability in organizations. Sustainable development is the central theme of the articles studied. Sustainable development is influenced by the ways that sustainability is measured within the network of which the organizations are a part of, including adequate systems, and is mediated by compatible behaviors. Originality/value: This study contributes to the literature by providing perspectives for future studies that may contribute to the sustainable development of organizations. Sustainable development is strongly influenced by the ways that sustainability is measured within the network of which the organizations are part, including appropriate systems, and is mediated by compatible behaviors.